Makna Profesionalisme Auditor dalam Implementasi Standar Audit: Studi Fenomenologi pada KAP Supriadi Laupe - Eva Nur Setyawati; Dhea Daleta; Chiky Salma (Lex: Journal of Social Sciences and Humanities Perspectives, 2026)
This study explores the meaning of auditor professionalism regarding the implementation of auditing standards at the Supriadi Laupe Public Accounting Firm in Palu City. Utilizing a qualitative approach with a phenomenological method, this study delves into the firsthand experiences of auditors in deeply practicing their professional duties. Data were gathered through in-depth interviews with senior auditors and reinforced by a literature review on auditing standards and the public accounting profession. The findings indicate that the value of professionalism is manifested in the structured application of auditing standards, spanning from the engagement, planning, execution, to the reporting phases. Furthermore, aspects of independence, professional skepticism, and professional judgment serve as vital foundations in evaluating materiality, audit risk, and the sufficiency of audit evidence. This study concludes that the integrity, objectivity, and professional responsibility of auditors play a crucial role in determining audit quality to maintain the credibility of financial statements and public trust.